Which patients with carpal tunnel syndrome are more associated with fibromyalgia syndrome? (Annals of Medical Research, 2023)
Aim: In this study, it was aimed to detect the presence of Fibromyalgia Syndrome (FMS) and related factors in patients diagnosed by Carpal Tunnel Syndrome (CTS).Materials and Methods: Demographic data and the features of CTS were noted by applying face-to-face questionnaire method. The existence of FMS in patients with CTS was investigated using the 2016 American College of Rheumatology (ACR) Fibromyalgia Diagnostic criteria. The Fibromyalgia Impact Questionnaire (FIQ) was introduced to patients diagnosed with FMS. Then, the correlations between the incidence of FMS in CTS patients, the presence of FMS and the hand with CTS, the severity of CTS and the existence of FMS were investigated. In addition, the relationship between the presence of FMS and the duration of CTS symptoms, and the severity of CTS and FIQ were also examined.Results: 151 patients included in the study. Bilateral CTS was detected in 89 (58.9%) patients. In patients with bilateral CTS, severity was classified as mild, moderate, or severe according to the worse hand. CTS was mild in 55 (36.4%), moderate in 87 (57.6%), and severe in 9 (6.0%) patients. Concomitant FMS was detected in 73 (48.3%) of all CTS patients. FMS rate is higher in patients with bilateral CTS (p=0.001). No significant relevance was observed between the severity of CTS and the presence of FMS (p = 0.864). The median duration of CTS symptoms with FMS patients was 24 (1-240) months; this period was found to be 12 (1-120) months in those without FMS. No significant relations between the presence of FMS and the duration of CTS symptoms were encountered (p = 0.073). The severity of CTS and FIQ demonstrated no significant difference (p=0.955).Conclusion: The case of FMS is high in specially bilaterally CTS patients. The fact that there may be common points in the pathogenesis of these two diseases suggests that it should be considered for diagnosis and treatment.